Precipitation analysis and water resource of Wadi Siham Basin, Yemen - Al Ward, Majed Ahmed; Ismail, Wan Ruslan (GEOGRAFI, 2019)
Wadi Siham Basin (WSB) is one of the significant agricultural areas in Yemen. This paper aims to analyse the quantity and spatial and temporal variation of rainfalls in WSB. The rainfalls (1979-2008) were collected and statistically analyses to evaluate the rainfall trends. The areal catchment rainfall was estimated using the Theissen polygon method, while the recurrence interval and probability analysis were carried out using the Hazen method. The Mann-Kendall and Sen’s slope analyses results showed that the rainfall at Wallan and Al-Amir stations had significant negative values (-4.72 mm/year and -6.11 mm/year respectively), while, the rainfall trend at Dhamar was positive at 50.20 mm/year. The total amount of rainfall was 1711.26 Mm3. The average annual rainfall in WSB was 346.39 mm/year. The mean annual water runoff was 82.92 Mm3 or 23.94% of the average annual rainfall in WSB. A total of 570 flood events occurred with a total volume of 53.10 Mm3 in a span of 20 years. The total water runoff was 4.85% of total volume of rain precipitated in WSB, indicating that the total water loss was 95.15%. In conclusion, the study has demonstrated the urgent need for a sustainable water resource management in WSB.